Antinomies of society essays of idealogies and institutions - Beteille, Andre (New Delhi Oxford University Press, 2000)
This volume is collection of essays that brings together work on institution, civil society and democracy all view in a comparative perspective with India. In exploring various facets of contemporary social and political life. Beteille reveals the stresse
Keywords: Ideology; Sociology-Philosophy